ANALISIS IMPLEMENTASI BUKU DURUSUL LUGHOH AL ARABIYYAH UNTUK MENINGKATKAN KETERAMPILAN BERBICARA BAHASA ARAB PADA SISWA KELAS X DI MADRASAH ALIYAH AL BAIRUNY SAMBONGDUKUH JOMBANG - Aisa, Aufia; Naba, Fajri Ainun (Universitas KH. A. Wahab Hasbullah, 2021)
The purposes of this research analysis of textbook implementation are to describe: the physical structure of textbook, the suitability of material in the textbook with Core Competencies and Basic Competencies with following the current developments of technology education, the accuracy of material in the textbook, the completeness of supporting material for learning skills especially in Arabic speaking skills, and the quality of the book Durusul Lughoh Al Arabiyyah in learning Arabic for students of class X MA Al Bairuny Sambong Dukuh Jombang. Based on the results of textbook analysis, it can be concluded that this textbook as a whole already has parts that should be in a textbook. The suitability of material description in the textbook with Core Competencies and Basic Competencies is included in feasible category, but lack of keeping up with current developments in education and technology. In this case, the completeness of learning support material in improving skills especially in Arabic speaking skills is very feasible and there are only a few shortcomings in the presentation of textbook including the lack of a table of contents and a simple dictionary in each chapter. Based on the results of research and discussion, obtained the conclusion that the book Durusul Lughoh Al Arabiyyah is categorized as a textbook with good quality to improve Arabic speaking skills.